Analysis of sensitivity to MK-801 treatment in a novel active allothetic place avoidance task and in the working memory version of the Morris water maze reveals differences between Long-Evans and Wistar rats - Valeš, Karel; Valešová, Věra; Klement, Daniel; Stuchlík, Aleš (Neuroscience research, 2006)
The aims of the present study were to compare the effect of subchronic administration of MK-801 on performance in the active allothetic place avoidance (AAPA) task and in the working version of Morris water maze (MWM) in Long-Evans and Wistar rats. Animals were trained for four daily sessions either in the AAPA or in the working memory version of the MWM. Wistar rats treated by MK-801 (0.1 mg/kg) showed a cognitive deficit in the AAPA task without a significant hyperlocomotion, whereas they were not impaired in the working memory version of the MWM compared to controls. Long-Evans rats treated by MK-801 (0.1 mg/kg) were not impaired either in the AAPA task or in the MWM task. Higher doses of MK-801 (0.2 and 0.3 mg/kg) produced hyperlocomotion in both strains which corresponded to an inability to solve both spatial tasks. Long-Evans rats were superior in the MWM to the Wistar rats in the groups treated with the low dose of MK-801. In conclusion, intact Wistar rats can efficiently solve both spatial tasks; however, they are more sensitive to MK-801-induced behavioural deficit. This has relevance for modeling of the schizophrenia-related deficits and for screening substances for their therapeutic potential.
Keywords: Memory, Short-Term; financování organizované; Animals; Dizocilpine Maleate; krátkodobá paměť; glutamátové receptory; Memory Disorders; Rats, Wistar; Excitatory Amino Acid Antagonists; hyperkineze; Orientation; Rats, Long-Evans; druhová specificita; Avoidance Learning; Space Perception; orientace; poruchy paměti; Species Specificity; Receptors, Glutamate; mozek; Financing, Organized; potkani Long-Evans; Male; dizocilpinmaleát; modely nemocí na zvířatech; Brain; učení vyhýbat se; Disease Models, Animal; nervový přenos; Synaptic Transmission; krysa rodu Rattus; vnímání prostoru; Hyperkinesis; Maze Learning; zvířata; mužské pohlaví; bludiště - učení; Rats; antagonisté excitačních aminokyselin; potkani Wistar